Intervention and Initiation of Anti-Bullying Policies in Schools : Praxis in Yogyakarta City Junior High Schools - Ariefa Efianingrum; Farida Hanum; Shely Cathrin; Maryani Maryani; Reno Wikandaru (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to describe policy interventions and innovative programs in anti-bullying praxis implemented in Yogyakarta City Junior High Schools. This study used descriptive methods with quantitative and qualitative approaches. This study was conducted in 2022 with 1517 students from 19 junior high schools in Yogyakarta City as participants. The participants of the study were principals and guidance and counselling teachers from 19 junior high schools in Yogyakarta City, junior high school supervisors, and policymakers at the Yogyakarta City Youth and Sports Education Office. The data collection techniques used were Focus Group Discussion (FGD), interviews, and documentation. The data were then analysed using qualitative descriptive analysis through several steps: data collection, condensation, data presentation, and conclusions. The findings indicate that the interventions made by schools on the phenomenon of bullying are: a) 69% of schools attempt to stop bullying; b) 64% of teachers reprimand perpetrators; c) 61% of teachers assist bullying victims; and d) 57% of teachers support bullying victims. In addition, qualitative data in the form of variations in the implementation of education policies in SMP Kota Yogyakarta to address bullying in schools were uncovered. According to the results of the study, there are: a) individual programs through counselling; b) collective mentoring through character building to develop soft skills and hard skills; c) rules of order and social control; and d) school partnerships with external institutions. These innovative programs are the outcome of the interpretation of educational policy by the institutions, as well as the creative initiatives of schools.